E-LEARNING PLATFORMS USED BY THE EFL TEACHER DURING DISTANCE LEARNING - Wirasatya, Gede Didit Ogi; Artini, Luh Putu; Wahyuni, Luh Gede Eka (Universitas Pendidikan Ganesha, 2021)
Due to the Covid-19 outbreak, learning activities had to be changed from face-to-face activities in class to distance learning. The e-learning platform has been essential to use since the covid-19 outbreak. However, online learning has several obstacles, such as the lack of facilities owned by students. Some parents and students face a problem during distance learning because they do not have a computer or android device. This study aims to analyze the bold learning platform used by EFL teachers during the covid-19 outbreak and analyze the use during distance learning. This research uses a descriptive qualitative approach. Observations and interviews were used as methods in this study. The subject of this research is an EFL teacher. This study indicates that EFL teachers entirely use WhatsApp as an e-learning platform to carry out teaching activities during distance learning using several steps. First, the teacher sends a greeting, reviewing the previous material and information on today's material. Second, the teacher provides additional material in e-modules and learning videos. Third, the teacher gives some assignments to students. Fourth, the teacher collects the collection of assignments. This research can be used as a reflection on how the implementation of classroom language used by the EFL teacher during distance learning.